Performance evaluation of Malathion biodegradation in batch and continuous packed bed bioreactor (PBBR) - Geed S.R.; Kureel M.K.; Giri B.S.; Singh R.S.; Rai B.N. (My University, 2025)
The aim of this work was to study the biodegradation of Malathion in batch and continuous packed bed (Polyurethane foam; PUF) bioreactor (PBBR). After 10 days, 89% Malathion removal was observed in batch PBBR. Continuous PBBR was operated at various flow rates (5–30 mL/h) under optimum condition over a period of 75 days. Inlet loading rates and elimination capacities were observed in the range of 36–216 and 7.20–145.4 mg/L/day with an average removal efficiency of more than 90% under steady state conditions. GC/MS analysis confirms phosphorodithionicacid,O,O,S-trimethylester and diethylmercaptosuccinate as metabolites. Biodegradation of Malathion under inhibitory and non-inhibitory conditions was studied using Monod and Andrew-Haldane models and the kinetic constants were calculated and found to be μmax: 0.271 per day; Ks: 126.3 mg/L using Monod and μmax: 0.315 per day; Ks: 151.32 mg/L; Ki: 594.75 mg/L using Andrew-Haldane models. © 2016 Elsevier Ltd